Clinical study on fibroadenoma of the breast - Rangaswamy, Purushothaman; Rubby, Shaikh Afzal (International Surgery Journal, 2016)
Background: It is a benign encapsulated tumour occurring commonly in young females of 15 -25 years of age. Presently it is considered as hyperplasia of a single lobule of the breast (classified under ANDI). Fibro-adenomas are one of the main benign diseases of breast. Though considered as a risk factor for development of breast cancer its reporting has been over shadowed by that of breast cancer. Methods: The study was undertaken during the period August 2014 to August 2016, patients who attended surgical outpatient as well as in patient of ESIC medical college hospital formed part of the study. Results: During the study period a total of 80 cases were confirmed as fibro-adenoma. The ages of cases ranged from 10-60yrs maximum number of cases 50 (62.5%) was in age group 16-30 years followed by 31 - 45 years with mean age of presentation 27 years. Majority of cases 60 (75.0%) belonged to urban background. It was found that 55 (68.75%) of the cases were married. Conclusions: Fibro-adenomas which is small, single, age <30 years can be left alone with regular follow - up with USG at 6 monthly interval. But anxiousness of patient and parents find difficult for this conservative approach.